2015
DOI: 10.1007/s00253-014-6318-y
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable source of omega-3 eicosapentaenoic acid from metabolically engineered Yarrowia lipolytica: from fundamental research to commercial production

Abstract: The omega-3 fatty acids, cis-5, 8, 11, 14, and 17-eicosapentaenoic acid (C20:5; EPA) and cis-4, 7, 10, 13, 16, and 19-docosahexaenoic acid (C22:6; DHA), have wide-ranging benefits in improving heart health, immune function, mental health, and infant cognitive development. Currently, the major source for EPA and DHA is from fish oil, and a minor source of DHA is from microalgae. With the increased demand for EPA and DHA, DuPont has developed a clean and sustainable source of the omega-3 fatty acid EPA through f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
146
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(157 citation statements)
references
References 56 publications
(79 reference statements)
0
146
0
1
Order By: Relevance
“…Concernant la production d'huile par voie fermentaire, on trouve de nombreux travaux à partir de la levure Yarrowia lipolytica menés par de multiples équipes de recherche qui visent à développer notamment des huiles pour biocarburants ou comme matière première pour la chimie (Thevenieau et al, 2008 ;Papanikolaou et al, 2009). Sur le plan industriel, on peut citer les développements de la société Dupont pour la production d'EPA (Xie et al, 2015), ou les travaux de la société Solazyme à partir de micro-algues pour produire différentes sortent de triglycérides (Solazyme, 2016). Concernant la bioconversion en molécules d'intérêt, on peut citer les travaux de multiples équipes autour de la production de biosurfactants par exemple (sophorolipides (de Oliveira et al, 2015), rhamnolipides (Kamaljeet, 2014), .…”
Section: L'opportunité Des Développements Technologiquesunclassified
“…Concernant la production d'huile par voie fermentaire, on trouve de nombreux travaux à partir de la levure Yarrowia lipolytica menés par de multiples équipes de recherche qui visent à développer notamment des huiles pour biocarburants ou comme matière première pour la chimie (Thevenieau et al, 2008 ;Papanikolaou et al, 2009). Sur le plan industriel, on peut citer les développements de la société Dupont pour la production d'EPA (Xie et al, 2015), ou les travaux de la société Solazyme à partir de micro-algues pour produire différentes sortent de triglycérides (Solazyme, 2016). Concernant la bioconversion en molécules d'intérêt, on peut citer les travaux de multiples équipes autour de la production de biosurfactants par exemple (sophorolipides (de Oliveira et al, 2015), rhamnolipides (Kamaljeet, 2014), .…”
Section: L'opportunité Des Développements Technologiquesunclassified
“…The whole genome sequence of strain CLIB122 [24] and a draft genome sequence of strain PO1f [25] have been published. Suitable genetic tools and transformation technologies have been developed [11,13,16,26]. In this review, we will focus on recent advances in metabolic engineering of Y. lipolytica for production of chemicals derived from acetyl-CoA, FA and lipids.…”
Section: Introductionmentioning
confidence: 99%
“…After three decades of studies, Yarrowia lipolytica has emerged as a preferred non-conventional yeast for metabolic engineering, especially for the production of chemicals derived from acetyl-CoA, fatty acids (FA) and lipids [11][12][13][14][15][16]. Y. lipolytica is a hemiascomycetous yeast, with a history of industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Based upon the results of this study, S. obliquus and N. muscorum show more promise for different PUFAs production and C. vulgaris revealed to be the more producer for other classes of fatty acids. Recently some newly emerged technologies such as metabolic engineering has been successfully exploited to increase the omega-3 production yield up to the highest known amounts in dry cell weight biomass in Yarrowia lipolytica yeast 29,30 . With increasing information on different microalgal genes and genomes, it could be suggested that genetic, metabolic and bioprocess engineering approach seem rational to maximize the microalgal production platform for PUFAs production.…”
Section: Figurementioning
confidence: 99%